Youths’ Roles in Candle Festival : Refection on Gaps between Learning Process and Local Culture Preservation in Ubonratchatani Province - Tapasilo, Dr. Phrakroobaideeka Supot; bundit, Asst. Prof. Dr.Phrakroowuttitham; Yannawaro, Phrasiwadech; Udomchodnamon, Chaiyasit; Srihamomgkon, Kaweepon (Journal for Developing the Social and Community, 2018)
The purpose of this research was to study the roles of adolescents in Candle Festival: Refection's on between learning process and local culture preservation in Ubonratchatani province on the social change process with local cultural economy on the way of life and the traditional values of candlelight traditions of Ubon Ratchathani community. And to study the cultural learning process of candlelit candle tradition of Ubon Ratchathani youth. The research results were found that; 1. The role of youth in the past with gratitude found that there is considered as cornerstone of life in every society. The old people create a conscious collective of the Lutheran community of their youth with company's tighter and more powerful of relationship of community's day to the past can be seen from traditional rituals are all being. The link between people in society in the past has been sliced for a long time, but has not gone through. The ancestral spirit is inherited with respect to relationship of course a factor in this. Into a unified one, the former Augustinian current becomes just a part Eternity which will come back to this at all Crutcher start new tradition at this terminal is to come back to methods of the past are present once again. The ancient traditions of local community at the Lent Candle Festival of Ubon Ratchathani not dissolved from consciousness of community, there was old man or new generation because as far as passing. The projected long-realization in imprinted deeply and firmly, the way of life and ideas of people in the community. 2. Traditional Candle parade The "wisdom" continue to be "local" cause "power landscape city" build a strong community. The community is solid. Issue of national importance in a "landscape Strength" Ubon Ratchathani Candle Festival honoring emulated. 3 Topmost institutions is nation Religion King Maintain dynasty to offer a candle. Worship the Buddha Faith of Thai nationality Taichung King Ideally, the Ubon Ratchathani to as "Candle Festival is social capital. The ancestors accumulated hundreds of years. The spirit and uniqueness of Ubon Ratchathani. Bringing the candlelight to the world to promote tourism. It is important to adhere to the essence of the candle. Then blend the original wisdom to harmonize perfectly. Do not be timid in nature, "the conservation of the original. Before promoting the new "It is the duty of the sons of Ubon to conserve and preserve the traditional candle endure forever remain an Ubon Ratchathani. 3. Educating and publishing tradition. The annual tradition of candles parade in Ubon Ratchathani. It is the inheritance of wisdom and contributes to the preservation of traditional folk culture. The rainy season of Ubon Ratchathani because the temple is worthwhile and the community is the center of candles and candles. Youth must want to do. Because the youth are important. Succession will take place, there must be faith to be done, there is a regional mind, how to show the importance of youth this point. The inheritance will happen because of the love and concern for the cooperation of the youth with the temple and the community. Finally, the state policy must be consistent and support the activities of the candlelit candles. To be able to inherit the wisdom of candle making in Ubon Ratchathani, the youth to the temple to do candles play a great role in the center of knowledge in the candlelit candles. Provide technical instruction in printing and carving candles at all stages. Let the child learn. And there is a relay. As well as find ways to make candles live long in the current situation. And wanted a government agency or an adult civil servant. To promote sustainable 4. Problem solving in conservation. The power of modernity and the impact on work values. Candle parade the candle festival is many. Especially in the contest too. Should compete creatively, harmony, goodwill by classifying the contest began to spread out development with a chance of winning, mixed together. How to solve this budgetary task? Each year there are problems to find a way to fix it over the years. There should be a fund to develop a candle festival. Solid concrete for example, "the Fund tents. Hakim baht apiece conservation candles in tents, "and so on. But that thought is always Candle Festival is a cumulative social capital for 100 year Have mental the spirit and uniqueness of Ubon Ratchathani to be preserved to survive the city of Ubon Ratchathani. Development will be able to make people happy. More comfort so invisible in the importance of preserving the cultural heritage of the village is no longer a concern. Consciousness to create Merit inheritance Conservation of traditions is just a reintroduction of the past to come back without feeling. The consciousness is created in the same tradition. So tradition is the only event the share of people in the village where all groups can participate. Without caste it celebrates the outsiders and everyone. They will be able to participate in the event does not feel different from others in the tradition. In addition, early morning came the power of the local government also gave the sky to the community lost the power to bargain. Making their own decisions goes to organizing the traditions to meet the celebrity. Entertainment, tourism and cultural community as the pace of change in the community. Have the same idea. Tradition does not respond. Common sense of the community is just a culture of entertainment. To be released into another society that can be re-created. Fun, jolly, may become a role model. It is a way to create understanding for the villagers. Young group the right teenagers are right, the sky is so local, and they are lost.